Pengaruh Gender Terhadap Kemampuan Pemecahan Masalah dan Penalaran Matematis Ditinjau dari Minat Belajar - Hary Prasetio Utomo; Aan Hendrayana; Yuyu Yuhana; Totok V.D. Saputro (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2021)
This study aims to compare problem skills and mathematical reasoning abilities based on gender in terms of interest in learning. This research is a quantitative research. The place used in this research is SMP N 1 PLAYEN. The subjects of this study were students of class VIII. This research uses descriptive quantitative research methods. The results of this study are (1) there is a management of problem skills and mathematical reasoning abilities based on gender (2) there are differences in problem abilities and mathematical reasoning abilities based on learning interests (3) there is an influence of the interaction of learning interest and gender on problem abilities and mathematical reasoning abilities